Cordon sanitaire, a necessary evil? Evaluation of non-pharmacological interventions against COVID-19 in Ovar, Portugal - Queiroz, Guilherme; Sá, Regina; Matos, Joana; Carmo, Susana; Ferreira, João Duarte; Pinho-Bandeira, Tiago; Leitão, Rui; Pereira, Tânia; Duarte, Iolanda; Costa, Celeste; Oliveira, Ana (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: From March 17 to April 17, 2020, the Portuguese municipality of Ovar was submitted to a cordon sanitaire due to a COVID-19 outbreak. During this period a whole Public Health structure had to be built up to respond to the healthcare needs of the population. The aim of this work is to contribute to the evidence on the efficacy of cordon sanitaire as an epidemic control strategy. Methods: All the major institutions in Ovar, both health and socially related, were called from the first day to form a Crisis Cabinet. Case tracking was assured by the creation of an online database. A major telephone network oversaw contact tracing, isolation mandates and surveillance. A massive testing structure was built up, and clinical assistance was assured by the local hospital and the Primary Care units. Patient referral to testing and clinical visits were made through online forms that allowed an efficient response and data for epidemiologic research. Results: A decline in the daily number of cases was seen after an incubation period (14 days), confirming lockdown was effective in blocking transmission chains. Besides, neighbouring municipalities were not significantly affected in relation to others. Lethality was bigger in Ovar than in whole Portugal. Conclusions: The decrease in the incidence, in the reproductive number and the non-affection of neighbouring municipalities appear to prove the cordon sanitaire as an effective Public Health measure to contain epidemics. However, an appropriate mitigation strategy must be adopted to conceal the challenge.